Dermal Squamous Cell Carcinoma in Broiler Chickens In Saskatchewan - Riddell, C. (1980)
A low but widespread incidence of a dermal squamous cell carcinoma is reported in broiler chickens in Saskatchewan. The tumor appears as an irregular ulcer in the skin and is widely distributed over the body of affected birds.